2023
DOI: 10.1039/d3fo01668d
|View full text |Cite
|
Sign up to set email alerts
|

Lychee pulp phenolics fermented by mixed lactic acid bacteria strains promote the metabolism of human gut microbiota fermentation in vitro

Abstract: Lychee pulp phenolics possess excellent biological activities, however, the phenolic substances changes after microbial treatments are unknown. Herein, the lychee pulp was fermented by L. plantarum, L. rhamnosus and the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Tang et al fermented Lychee pulp with a combination of bacteria, significantly increasing the release of catechins and quercetin. Moreover, the fermented lychee phenolics were found to be more beneficial for the growth of gut microbiota [ 25 ]. Similarly, Wang et al indicated that dietary supplementation with 3% fermented Artemisia argyi significantly enhanced the growth performance and meat quality of broilers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al fermented Lychee pulp with a combination of bacteria, significantly increasing the release of catechins and quercetin. Moreover, the fermented lychee phenolics were found to be more beneficial for the growth of gut microbiota [ 25 ]. Similarly, Wang et al indicated that dietary supplementation with 3% fermented Artemisia argyi significantly enhanced the growth performance and meat quality of broilers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the gut microbiota status was most favorable in the samples fermented by lactic acid bacteria. This may be attributed to the ability of lactic acid bacteria to convert phenolic compounds in lychee into smaller molecules, which is more favorable for the metabolism and transformation of the gut microbiota [83]. Compared with unfermented papaya puree, Leuconostoc pseudomesenteroides 56 fermented papaya puree had the highest concentrations of protocatechuate, coumaric acid, and ferulic acid after 7 days of storage at 4 • C, and the inhibition of intestinal α -glucosidase activity by phenolic compounds is considered to serve as a mechanism to exert an antidiabetic effect.…”
Section: Phenolic Compoundsmentioning
confidence: 99%